THE DETERMINATION ACCOUNTING CONSERVATISM IN THE INDONESIA BANKING SECTORS - Saputri Mashuri, Ayunita Ajengtiyas; Praptiningsih (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2024)
The objective of study is to analyze the significant influence of growth opportunities, bonus plans, political costs, tax incentives and CEO pensions on accounting conservatism in banking sector companies listed on the Indonesia Stock Exchange for the 2020-2022 period.. This research uses secondary data in the form of annual reports and company financial reports with a research sample of 43 banking companies. The analytical method used is panel data regression analysis with SPSS version 14 data processing tools. The results of this research shows growth opportunities, bonus plans, political costs and CEO retirement do not have a significant effect on accounting conservatism. Otherwise, tax incentives have a significant effect on accounting conservatism.